Dispute over Double Certificate on the National Land Agency of Indramayu District - Titi Resmiyanti; Akhmad Khisni; Achmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) Analyze the dispute resolution on dual certificates in the National Land Agency Indramayu district, 2) Barriers and Solutions Upon completion of Certificate Associate at the National Land Agency Indramayu district.The approach used in this paper is empirical sociological juridical with the help of primary data or empirical data as the main data. Sociological research empirical law is a legal research methods that identify and conceptualize law as a social institution rill and functional in a real life system. The data collection was obtained by interview and literature. The data were analyzed qualitatively normative.The research results are: 1). Settlement of disputes over double certificates in the National Land Agency Indramayu district that summons to the parties to the dispute to mediation. If mediation is not successful then the case was continued with the proceedings. The process of settlement is with the trial. Aspects that influence the judge determines the choice of action in the resolution of a dispute ie double certificate in terms of proof, because the facts and events as the principal case will be known judge from the evidence submitted by the parties to the dispute 2). Obstacles in solving the double certificate in Indramayu district that is party to the dispute does not come in mediation, data submitted on the land question is not clear, each party wants to win the case and the importance of their own interests. Solutions that can be done is the mediator to give some advice to the parties so that more can cooperate in following the legal process, so that the process can be completed justice and it takes a long time.Keywords: Dispute; Double Certificate; BPN.